Perkembangan Pendidikan di Tarutung Masa Kolonial - Oktavia Nasrani Tampubolon; Ayu Rizkiya; Abdul Haris Nasution (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to see how the development of education in Tarutung during the Dutch Government. The method used is the Historical research method. The stages in the historical research method consist of four stages (heuristics, verification, interpretation, and historiography). The results of the study concluded that one of the backgrounds of the Dutch Government was to open educational institutions in Tarutung, one of which was so that the Batak people could accept the Dutch presence to control North Tapanuli. The development of education for the Batak people by the Dutch, only followed the renewal movement that had been carried out by the mission. The missionaries have managed to get close to the Batak people. Even the German mission managed to Christianize the Batak people, they helped the Dutch to take control of Tapanuli. In the late 19th to early 20thcenturies, several schools and hospitals were built in Tarutung by the Dutch government. The Batak people are getting to know the outside world more and more. The Batak people also know a lot of letters and know numbers. Many young men have received education, and some continue their education to Batavia.